PERAN KEPUASAN KERJA DAN KOMITMEN ORGANISASI PADA INTENTION TO QUIT DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR DI UPTD RUSUNAWA SLEMAN - Aulia, fikri Budi; Wahyudi, Danang; Sunyoto, Danang; Puryanti, Puryanti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Objectives–This study aims to examine and analyze the role of job satisfaction and organizational commitment on intention to quit and organizational citizenship behavior. Design/Methodology - The population of this research is 74 employees of UPTD Rusunawa. The research model uses the census model. The research method is quantitative with instrument test, classical assumption test, and multiple regression analysis. Results - job satisfaction and organizational commitment each play a significant role in intent to quit and OCB at UPTD Rusunawa Sleman. Originality – Research still needs to be done with other research objects that have the same characteristics, and this research can add references for further research.